2021
DOI: 10.3390/rs13214365
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Verification and Correction of D-InSAR and SBAS-InSAR in Monitoring Mining Surface Subsidence

Abstract: The accuracy of InSAR in monitoring mining surface subsidence is always a matter of concern for surveyors. Taking a mining area in Shandong Province, China, as the study area, D-InSAR and SBAS-InSAR were used to obtain the cumulative subsidence of a mining area over a multi-period, which was compared with the mining progress of working faces. Then dividing the mining area into regions with different magnitudes of subsidence according to the actual mining situation, the D-InSAR-, SBAS-InSAR- and leveling-monito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…AHP is a flexible quantitative method, which has become one of the commonly used methods in risk assessment [60][61][62][63][64]. Based on the relevant literature and engineering requirements to determine the influencing factors affecting the surface subsidence monitoring program [14,[65][66][67], a total of three primary indicators and 16 secondary indicators are included, as shown in Figure 4 (natural factors and target constraints are determined in advance):…”
Section: Preference Model 231 Infactors Determination and Analysismentioning
confidence: 99%
“…AHP is a flexible quantitative method, which has become one of the commonly used methods in risk assessment [60][61][62][63][64]. Based on the relevant literature and engineering requirements to determine the influencing factors affecting the surface subsidence monitoring program [14,[65][66][67], a total of three primary indicators and 16 secondary indicators are included, as shown in Figure 4 (natural factors and target constraints are determined in advance):…”
Section: Preference Model 231 Infactors Determination and Analysismentioning
confidence: 99%
“…Therefore, due to the differences in scattering characteristics in different areas of variable radar reflection regions, whether it is sparse persistent scatterers with high coherence or the interferometric fringe, this will make the single traditional interferometry methods, such as PS-InSAR or SBAS-InSAR, have limitations. At present, some studies [25][26][27][28] have only simply superimposed the two techniques and failed to consider the advantages and disadvantages of each of them. Experience with using PS-InSAR and SBAS-InSAR has shown that PSCs with higher-order coherence in PS-InsSAR are generally distributed in those point targets of urban built-up areas, and SDFP pixels in SABS-InSAR are generally distributed in those distributed targets of countryside vegetation areas, which causes PS-InSAR to have better accuracy in urban built-up areas, and SABS-InSAR has better accuracy in countryside vegetation areas.…”
Section: Introductionmentioning
confidence: 99%
“…However, SBAS-InSAR is only applied to pixels exhibiting a sufficiently high coherence degree [40][41][42][43][44][45]. Chen et al accurately identified the location, range, spatiotemporal change trend, and basin edge subsidence information of subsidence mining in Shangdong Province, China using DInSAR and SBAS-InSAR, and verified and corrected the subsidence results using leveling [46]. Pawluszek-Filipiak et al studied the mining subsidence of the Rydultowy coalfield in Poland by combining the advantages of both DInSAR and SBAS-InSAR techniques and found that the obtained results were in good agreement with leveling data [47].…”
Section: Introductionmentioning
confidence: 99%